Cover Image. (18th February 2020) - Abbasi, Nimrah; Cortes, Magda Sanz; Ruano, Rodrigo; Johnson, Anthony; Morgan, Tara; Coleman, Beverly; Baschat, Ahmet; Zaretsky, Michael; Lim, Foong Yen; Bulas, Dorothy; Benachi, Alexandra; Ryan, Greg; et al.
Abstract : The cover image is based on the Original Article * Variability in antenatal prognostication of fetal diaphragmatic hernia across the North American Fetal Therapy Network (NAFTNet) by Nimrah Abbasi** et al., https://doi.org/10.1002/pd.5668 .***